BRANCHING PATTERNS OF INDIVIDUAL SYMPATHETIC NEURONS IN CULTURE - Bray, D. (The Rockefeller University Press, 1973)
The growth of single sympathetic neurons in tissue culture was examined with particular regard to the way in which the patterns of axonal or dendritic processes (here called nerve fibers), were formed. The tips of the fibers were seen to advance in straight lines and to grow at rates that did not vary appreciably with time, with their position in the cell outgrowth, or with the fiber diameter. Most of the branch points were formed by the bifurcation of a fiber tip (growth cone), apparently at random, and thereafter remained at about the same distance from the cell body. It seemed that the final shape of a neuron was the result of the reiterated and largely autonomous activities of the growth cones. The other parts of the cell played a supportive role but, apart from this, had no obvious influence on the final pattern of branches formed.